Co‐cultivation of Thermoanaerobacter strains with a methanogenic partner enhances glycerol conversion. Issue 4 (10th March 2020) - Magalhães, Carla Pereira; Ribeiro, Joaquim A.; Guedes, Ana P.; Arantes, Ana L.; Sousa, Diana Z.; Stams, Alfons J. M.; Alves, Maria M.; Cavaleiro, Ana Júlia
Summary: Glycerol‐rich waste streams produced by the biodiesel, bioethanol and oleochemical industries can be treated and valorized by anaerobic microbial communities to produce methane. As current knowledge of the microorganisms involved in thermophilic glycerol conversion to methane is scarce, thermophilic glycerol‐degrading methanogenic communities were enriched. A co‐culture of Thermoanaerobacter and Methanothermobacter species was obtained, pointing to a non‐obligately syntrophic glycerol degradation. This hypothesis was further studied by incubating Thermoanaerobacter brockii subsp. finnii and T. wiegelii with glycerol (10 mM) in pure culture and with different hydrogenotrophic methanogens. The presence of the methanogen accelerated glycerol fermentation by the two Thermoanaerobacter strains up to 3.3 mM day −1, corresponding to 12 times higher volumetric glycerol depletion rates in the methanogenic co‐cultures than in the pure bacterial cultures. The catabolic pathways of glycerol conversion were identified by genome analysis of the two Thermoanaerobacter strains. NADH and reduced ferredoxin formed in the pathway are linked to proton reduction, which becomes thermodynamically favourable when the hydrogen partial pressure is kept low by the hydrogenotrophic methanogenic partner. Abstract : Glycerol is an important by‐product of the biodiesel and bioethanol industries, which results in a surplus of this compound. We investigated anaerobic glycerol fermentation coupled to methane production at high temperature (65°C), as a potential strategy for the valorization of this industrial by‐product. We discovered that glycerol fermentation by Thermoanaerobacter strains was much faster when performed in cooperative relationship with a hydrogenotrophic methanogenic partner. The methanogen facilitates glycerol conversion by consuming the hydrogen, thus assisting in the redox balance.